(untitled) (Journal of Pedagogical Inventions and Practices, 2022)
The article discusses the features of the methodology of teaching and learning English in the twentieth century, as well as the importance of training highly qualified personnel and improving the quality of education, mastering the requirements of world standards for teaching English in the modern education system.